Political Communication in Television Media: A Study of Encoding/Decoding on Voters in the 2024 Election - Iswarinda, Michella; Dewi, Evie Ariadne Shinta; Bakry, Gema Nusantara (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
This study analyzes the role of the media in shaping public opinion ahead of the 2024 Presidential Election, focusing on the Maghrib adhan broadcast featuring Ganjar Pranowo on MNC Group television station in September 2023. This phenomenon raises polemics regarding media independence, given that MNC Group is owned by Hary Tanoesoedibjo, chairman of the Perindo Party who supports Ganjar as a presidential candidate. The broadcast is considered an attempt at identity politics to build a politician's image. This research uses a critical paradigm with a qualitative descriptive approach, combining Stuart Hall's encoding-decoding theory and Roland Barthes' semiotics to analyze the political symbols in the broadcast. Data collection was done through in-depth interviews, observation, and literature study. The results show that political shows are not taken for granted by the audience, but through a decoding process that is influenced by their social and cultural background. The media, in this case RCTI, utilizes symbols and narratives to shape the image of politicians, although the meaning received by the audience varies, depending on their decoding position. This finding confirms the role of the media as a tool of domination in shaping public opinion and creating political hegemony, which risks reducing the objectivity and independence of the media in a democracy.